Alla ricerca della completezza: il borghese tra comico e serio - Tortonese, Paolo (Status Quaestionis, 2017)
Is the bourgeois a serious character? According to Auerbach’s theory upon Realism, the comic portrait of middle class, as the one Molière made, should have been disappeared in the 19th century; however, the bourgeois is still ridiculous, in the theatre as well as in the caricature and even in the novel. The middle class nature itself allows the application of comical mechanisms: the middle class is ‘in the middle’, between lower and upper classes, marked by its ‘halfness’. Ralph Waldo Emerson said that «the essence of all jokes, of all comedy, seems to be an honest or well-intended halfness». This paper aims to show the double feature – comic and tragic – of the bourgeoisie, underlining its representation and contradictions throughout the ‘serious century’.